2021
DOI: 10.1029/2020jd033291
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Extreme Warm‐Air Advection in the Arctic During Summer: The Effect of Mid‐Latitude Pollution Inflow on Cloud Properties

Abstract: Usually the Arctic is relatively free of anthropogenic influence in summer, which means that particles from natural sources can be the most significant nuclei for cloud droplets. However, this is not the case during anomalously warm‐air intrusions when the air origin comes from lower latitudes. In this modeling study, we investigate the effect of mid‐latitude pollution inflow (anthropogenic and biomass burning [BB]) on the aerosol‐cloud‐radiation interactions during an episode of extreme warm‐air advection. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 121 publications
(223 reference statements)
0
5
0
Order By: Relevance
“…On the contrary, studies of summer events are limited, although the presence of sunlight in this season makes climate implications even more complex (Tjernström et al, 2019;You et al, 2021). Recently, a few studies reported a correlation between pollution transport to the Arctic with warm-air intrusion based on the analysis of single events in summer and late spring (Bossioli et al, 2021;Dada et al, 2022). Our results verified the consistency of such pattern with longer time series and highlighted the need to further investigate the implications of warm-air intrusion in the warm periods, when background aerosol concentration is lower and these events can alter substantially aerosol population climate-relevant properties (Dada et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, studies of summer events are limited, although the presence of sunlight in this season makes climate implications even more complex (Tjernström et al, 2019;You et al, 2021). Recently, a few studies reported a correlation between pollution transport to the Arctic with warm-air intrusion based on the analysis of single events in summer and late spring (Bossioli et al, 2021;Dada et al, 2022). Our results verified the consistency of such pattern with longer time series and highlighted the need to further investigate the implications of warm-air intrusion in the warm periods, when background aerosol concentration is lower and these events can alter substantially aerosol population climate-relevant properties (Dada et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Biogenic emissions are calculated online with the MEGAN module (Guenther et al 2006) while the initial and boundary conditions for gases and aerosols come from simulation of CAM-chem in CESM2.0 (Emmons et al 2020). For the other physical parameterizations and information on natural and fire emissions, the reader is referred to the setup of Bossioli et al (2021).…”
Section: Wrf-chem Operated By Nkuamentioning
confidence: 99%
“…Such observations indicate both the long‐range transport and local supply of aerosol over the Arctic. The combination of natural and anthropogenic BB sources can have a strong effect on cloud properties and the radiation budget (Bossioli et al., 2021).…”
Section: Introductionmentioning
confidence: 99%